Pelatihan Pembuatan Nata Belimbing sebagai Upaya Pemberdayaan Masyarakat Kelurahan Karangsari Kota Blitar Menuju Desa Mandiri Pangan - Eva Nurul Malahayati; Mar'atus Sholihah; Luthfiya Aqidatu Shoolikhah; Sholicatul Amin (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Karangsari is the largest producer of Karangsari starfruit varieties in Blitar City. To support community food security as well as to preserve the Karangsari star fruit variety and promote the economy of the community in Karangsari village, most of the people's yards are used as star fruit orchards. Karangsari star fruit harvest is usually sold in the form of fresh fruit. This fresh fruit does not have a long shelf life. During the harvest season, star fruit prices tend to be low. Overripe fruit, defects due to insect bites, and those that do not match the sales size grade are usually just thrown away and not used. As a result, the income of farmers has decreased. The target focus of this community service activity partner is the UMK community group in the Karangsari village. The priority problem from partners is the lack of partner skills in processing star fruit, especially those that do not sell due to overripe or slightly defective (damaged) and do not match the sales size grade. This activity aims to improve the skills of partners in making nata de Averrhoa carambola as a processed product of Karangsari starfruit which can be used as the flagship product of MSEs in Karangsari. In this activity there are several methods carried out, namely (a) providing material on the technique of making nata de Averrhoa carambola, (b) training in making nata de Averrhoa carambola, and (c) assistance in processing nata de Averrhoa carambola so that it becomes ready-to-eat food or drink. for consumption and sale. Through this training activity, the Karangsari UMK group has the understanding and skills in processing starfruit into nata. In addition, the MSE group is motivated to develop superior products from star fruit nata. However, the packaging and labeling of processed nata products is still less attractive to consumers. Therefore, it is necessary to continue with special training related to packaging and labeling of processed nata products that are more attractive and have a selling value.